Pengaruh ROA, NPM, EPS Terhadap Return Saham Pada Emiten Jakarta Islamic Index Tahun 2010-2013 - Syahputri, Rianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this research is to investigate the significant effect of the variables Return On Asset and Net Profit Margin as well as the Earning Per Share partially and simultaneously to the stock return of sharia stock that were listed on Jakarta Islamic Index period 2010-2013. The approach that is used is the quantitative approach using regression analysis the data panel with four variables return on asset, net profit margin and earning per share as exogenous variable and stock return as endogenous variable. The companies that are used for this research are Astra Agro Lestari Tbk, Astra Internasional Tbk, Alam Sutera Realty Tbk, Charoen Pokphand Indonesia Tbk, Indocement Tunggal Prakarsa Tbk, Indo Tambangraya Megah Tbk, Kalbe Farma Tbk, Lippo Karawaci Tbk, PP London Sumatra Indonesia Tbk, Tambang Batubara Bukit Asam (Persero) Tbk, Semen Indonesia (Persero) Tbk, Telekomunikasi Indonesia (Persero) Tbk, United Tractors Tbk, Unilever Indonesia Tbk. The data that is used is a secondary data. All data are gathered from the annual financial report of the period 2010-2013.